(untitled) (Proceedings of International Educators Conference, 2024)
Eclampsia is a leading disease during pregnancy, occurring alongside the development of multiple organ failure. Studying its etiology and pathogenesis remains a pressing issue for many researchers. The complications of eclampsia in various diseases include obstetric hemorrhage, placental abruption, placental insufficiency, fetal growth restriction syndrome, HELLP syndrome, and severe cerebrovascular pathologies in women. The course of eclampsia and its complications reduces the quality of life for patients, which is related to the high prevalence of cardiovascular diseases. The development of this pathological process in the body of a pregnant woman leads to high maternal and perinatal morbidity and mortality rates. Modern statistical data confirm this: the proportion of eclampsia among pregnancy complications ranges from 10.1% to 20%, accounting for 21.3% of maternal mortality causes. In developing countries, eclampsia remains a leading cause of maternal deaths (40-80%).